Lineage-Specific Genes and Cryptic Sex: Parallels and Differences between Arbuscular Mycorrhizal Fungi and Fungal Pathogens. (February 2021) - Reinhardt, Didier; Roux, Christophe; Corradi, Nicolas; Di Pietro, Antonio
Abstract : Arbuscular mycorrhizal fungi (AMF) live as obligate root symbionts on almost all land plants. They have long been regarded as ancient asexuals that have propagated clonally for millions of years. However, genomic studies in Rhizophagus irregularis and other AMF revealed many features indicative of sex. Surprisingly, comparative genomics of conspecific isolates of R. irregularis revealed an unexpected interstrain diversity, suggesting that AMF carry a high number of lineage-specific (LS) genes. Intriguingly, cryptic sex and LS genomic regions have previously been reported in a number of fungal pathogens of plants and humans. Here, we discuss these genomic similarities and highlight their potential relevance for AMF adaptation to the environment and for symbiotic functioning. Highlights: Genome analysis in arbuscular mycorrhizal fungi (AMF) reveals intraindividual nuclear homogeneity combined with high interstrain diversity. The high number of lineage-specific (LS) genes in AMF genomes is reminiscent of the rapidly evolving LS regions found in plant pathogens. These regions encode secreted effectors and other virulence factors, as well as an expanded set of signaling components such as protein kinases, suggesting a similar role in perception and interaction with the abiotic and biotic environment in AMF. Genomes of AMF and fungal pathogens exhibit parallels in the amplification of gene families related to signaling; by contrast, predicted secreted effector genes of AM tend to be more conserved (encoded by core genes), while effectors of pathogens are often encoded by LS genes. AMF retain most of the genetic machinery required for sex, show evidence of ongoing recombination, and can form pseudo-dikaryons. However, the existence of meiotic cells or other (para)sexual stages has yet to be experimentally confirmed.